Meeting the Challenges of Chemical and Biological Weapons: Strengthening the Chemical and Biological Disarmament and Non-proliferation Regimes - Edwards, Brett; Novossiolova, Tatyana; Crowley, Michael; Whitby, Simon; Dando, Malcolm; Shang, Lijun (Frontiers in Political Science, 2022)
Challenges arising from chemical and biological weapons can arise from natural, accidental, and deliberate causes. These challenges need to be met by an integrated strategy that deals with all such diseases and poisoning in humans, animals and plants, and involves experts from different subject areas such as chemistry, biology, life sciences and social sciences. This paper is concerned with the challenges of deliberate disease and poisoning but is linked to the broader concept of the problem in a holistic one health approach. The challenge of deliberate disease or poisoning from chemical and biological agents also has to be integrated at an international level through the Chemical Weapons Convention (CWC) and the Biological and Toxin Weapons Convention (BTWC) during this period of rapid and converging advances in science and technology and international instability. Together with the 1925 Geneva Protocol these Conventions form the foundation built up during the last century to prevent the use of chemical, biological and toxin weapons from being used and thereby attempting to minimise the challenge at the source. During this century despite the agreement of some positive measures to strengthen these Disarmament and Non-Proliferation Regimes, there is little doubt that both are facing considerable difficulties at present. However, there is a long and diverse tradition of civil society efforts to help strengthen these regimes and there is some hope that, following the dangers from biological agents exposed in the pandemic, States Parties will be able to find ways to improve the protection afforded by the two Conventions. This paper describes one such civil society project designed to help achieve progress at the 9th Review Conference of the BTWC in 2022 and the 5th Review Conference of the CWC in 2023. The six social and life scientists involved in the project published a detailed report analysing the options available to States Parties at these review conferences and then attempted to raise awareness of these options amongst politicians and the general public through the media, and through a widely attended webinar and a series cartoons developed with professional artists. The key findings and policy recommendations are outlined.